CROSSFIT AND RECURRING JOINT INJURIES - Pereira Gomes, Adilson; Maria Santos de Aguiar, Débora (Health and Society, 2023)
CrossFit is an intense and multifaceted physical training modality that has gained a lot of popularity in recent years. However, it has also raised concerns about the risk of injury, especially to the joints. Recurrent joint injuries are a relevant concern for CrossFit practitioners, as the modality involves high-intensity movements, such as weight lifting, jumping, running and exercises that place significant pressure on the joints. Joint injuries in CrossFit can occur due to a variety of reasons, including lack of proper technique, overload, lack of adequate warm-up, muscle fatigue, and repetitive movements. The joints most susceptible to injury include the shoulders, knees, hips and wrist joints. Joint injuries can range from mild to severe and can include strains, sprains, cartilage injuries and even ligament tears. To prevent recurring joint injuries during CrossFit practice, it is essential that practitioners receive adequate guidance from a qualified trainer. This includes learning the correct technique for each movement, not exceeding personal load limits, warming up thoroughly, and taking appropriate recovery measures after training. Furthermore, listening to your own body and respecting signs of fatigue and pain is essential to avoid injuries. The present study aims to identify recurrent injuries in CrossFit. The methodology used to prepare the study is qualitative research, through a bibliographic review. It is concluded that CrossFit is a challenging modality that can expose practitioners to the risk of recurrent joint injuries, especially when inadequate technique and lack of safety precautions are involved. With the correct guidance, adequate training and respect for personal limits, it is possible to minimize these risks and enjoy the benefits of CrossFit in a safer and healthier way.